2021
DOI: 10.1101/2021.06.15.21258966
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tocilizumab in COVID-19 – A Bayesian reanalysis of RECOVERY

Abstract: Background: Randomised Evaluation of COVID-19 Therapy (RECOVERY) demonstrated that tocilizumab reduces mortality in hospitalized COVID-19 patients. However, substantial uncertainty remains whether tocilizumab's effect is similar across clinically relevant subgroups. Whether this uncertainty can be resolved with Bayesian methods is unknown. Design, Setting, Participants, and Interventions: RECOVERY was a controlled, open-label, platform UK trial that randomized (1:1) 4116 adults with oxygen saturation <92% … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Our research group has previously reanalyzed the association of tocilizumab with clinical outcomes in different COVID-19 subgroups of patients while focusing on the RECOVERY trial . However, we did not collect and analyze data limited to patients using corticosteroids in different respiratory subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…Our research group has previously reanalyzed the association of tocilizumab with clinical outcomes in different COVID-19 subgroups of patients while focusing on the RECOVERY trial . However, we did not collect and analyze data limited to patients using corticosteroids in different respiratory subgroups.…”
Section: Discussionmentioning
confidence: 99%
“…However, subsequent meta-analyses of more recently completed RCTs including RECOVERY, or even unpublished data through searches of electronic databases and contact with experts, ultimately concluded that, in patients hospitalised with COVID-19, treatment with IL-6 antagonists, and in particular tocilizumab (with much higher certainty than sarilumab, but not siltuximab), results into a significant reduction in 28-day all-cause mortality ( 2 , 32 , 58 ), in line with previous meta-analyses of observational cohort studies ( 22 , 77 , 78 ). Specifically, high probability of reduced risk of mortality and clinically meaningful mortality benefit was observed in patients receiving concomitant glucocorticoids and non-invasive ventilation or high-flow oxygen, with no need of IMV or cardiovascular support ( 32 , 79 ). A significant interaction was seen in the subgroup analysis in regard to concomitant steroid therapy ( 2 ), while other meta-analyses confirmed the independent strong benefit of steroid therapy, particularly low-dose dexametasone (not high-dose methylprednisolone or hydrocortisone), on survival of severe and critical patients ( 80 ).…”
Section: Confirmations From Meta-analyses and Current Guidelinesmentioning
confidence: 99%
“…One article was not accessible and thus it was excluded. 19 After evaluating the other 92 articles for eligibility, 42 were excluded for the following reasons: one study investigated tocilizumab combined with another IL‐6 inhibitor, 20 two discussed therapies other than tocilizumab, 21 , 22 37 were not systematic reviews, 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 and two were systematic reviews of preclinical or animal studies. 60 , 61 Finally, 50 articles met the eligibility criteria and were included in the present umbrella review 6 , 28 , 62 , 63 , 64 , 65 ,…”
Section: Resultsmentioning
confidence: 99%